Readjustment of Capsule Endoscopy Protocols to the COVID-19 Pandemic in a Portuguese Tertiary Center - Correia, João; Ponte, Ana; Gomes, Catarina; Afecto, Edgar; Estevinho, Maria Manuela; Rodrigues, Adélia; Pinho, Rolando; Carvalho, João (Turkish Journal of Gastroenterology, 2022)
Background: The prevention of severe acute respiratory syndrome corona virus 2 transmission implies several social distancing mea- sures, imposing a change in the protocols of several hospital departments. Capsule endoscopy protocols changes were implemented and evaluated in a Portuguese tertiary center. Methods: The authors compared pre-pandemic and peri-pandemic protocols, the latter favoring social distancing, used in MiroCam (IntroMedic, Seoul, Korea) and PillCam Crohn (Medtronic, Minneapolis, Minn, USA) capsule endoscopy, in a Gastroenterology Department of a tertiary center. All capsule endoscopy performed in outpatients between February 2018 and September 2020 was included. The authors compared significant lesions detection rate, completeness of procedure, adequate bowel preparation, complications rate, and patient satisfaction (through a brief phone call survey) among the protocols. Results: This study included 70 MiroCam CE and 43 PillCam Crohn capsule endoscopy. No statistically significant differences concern- ing performance measures and patients satisfaction were found among the pre-pandemic protocol and the peri-pandemic protocol in MiroCam capsule endoscopy. Conversely, in PillCam Crohn capsule endoscopy, the rate of complete exams was significantly inferior in the peri-pandemic protocol (84.8% vs 50.0%, P = .036), with no other statistically significant differences in the remaining parameters. Conclusion: The performance measures and patient satisfaction were similar among the protocols analyzed for MiroCam capsule endoscopy. Thus, the readjustment of this capsule endoscopy system, which favors a reduction in hospital stay, appears to be a good alternative to the former protocols in this pandemic era. In contrast, the rate of complete exams was significantly inferior in the adapted protocol to the pandemic era for PillCam Crohn capsule endoscopy, disfavoring its maintenance in the clinical practice.